TO EVALUATE THE IMPORTANCE OF HYPOTENSIVE THERAPY WITH B-ADRENOBLOCKERS AND INDIRECT ANTICOAGULANTS IN THE FORMATION OF PERSISTENT ERYTHEMA OF THE FACIAL SKIN ROSACEA - Toshev S.U.; Rafikova M.F.; Isaev X.D. (PEDAGOGS, 2024)
Abstract: The task set before us to write this article was to evaluate the importance of antihypertensive therapy with β- blockers and indirect anticoagulants in the formation of persistent erythema of the facial skin rosacea . To achieve our goals and objectives, we analyzed the comparative dynamics of vascular changes on the skin of the face by measuring the acoustic conductivity of the skin in patients with post-infarction cardiosclerosis and arterial hypertension against the background of antihypertensive therapy. As a result, we came to the conclusion that a timely transition to a combined antihypertensive drug, exforge , will significantly reduce the risk of the formation of persistent erythema and rosacea in patients with a predisposition to the development of this dermatosis.